Preliminary evidence-based recommendations for return to learn: a novel pilot study tracking concussed college students - Zachary W Bevilacqua; Mary E Kerby; David Fletcher; Zhongxue Chen; Becca Merritt; Megan E Huibregtse; Keisuke Kawata (Concussion)
Aim: Students re-entering the academic setting after a concussion is commonly referred to as return-to-learn and, to date, very few studies have examined the return-to-learn aspect of concussion recovery. Methodology: Nine college-aged, full-time students who were diagnosed with concussions were monitored throughout their concussion recovery. The severity for five chief symptoms (headache, dizziness, difficulty concentrating, fatigue, anxiety) were recorded six-times per day through text messages, and daily phone calls recorded participant's behavioral traits. Results: We identified five behavioral variables which significantly influenced symptom resolution (music, sleep, physical activity, water and time) (p = 0.0004 to p = 0.036). Additionally, subjects reported math and computer-oriented courses as the most difficult (33 and 44%, respectively). Conclusion: We introduce a novel approach to monitor concussed students throughout their recovery, as well as factors that may influence concussion recovery process.